Family logotherapy - Sipowicz, Kasper; Podlecka , Marlena; Pietras, Tadeusz (Kwartalnik Naukowy Fides et Ratio, 2022)
The paper outlines the concept of family logotherapy in relation to systemic family therapy, popular in Poland. The basic philosophical and anthropological assumptions of Frankl’s logotherapy, and thus the phenomenon of free will, as well as the will to make sense and to find the meaning of life are discussed. Referring to the systemic family therapy dominant in the Polish discourse, the basic assumptions, goals and structure of family logotherapy are presented, according to which the conscious values, senses and meanings of individual members shape the pattern of interactions within the family.